Control interno y la gestión de inventarios en la empresa Telecable Iquitos SAC, periodo 2022 - Sullon Amaringo, Dayana Josetty; Yong Gola, Felipe Antonio (Universidad Nacional de la Amazonía Peruana, 2023)
The present research work had the general objective of determining the relationship between internal control and inventory management in the company Telecable Iquitos SAC, period 2022, quantitative research, with a cross-correlational design type and non-experimental design; had 76 workers as study population, and a record of control reports made in the company Telecable Iquitos SAC, period 2022, the investigation concluded that according to the field of study there is a very high correlation between the internal control variable and Inventory management , given that according to the results the degree of correlation is in the range of 0.80-0.99 (very high correlation) being a very significant correlation since the value of Sig. (bilateral) is 0.01; Therefore, it can be affirmed that it has a 99% confidence level, so the general hypothesis is accepted, in addition to recommending that the company periodically disseminate internal control activities, in order to keep everyone involved in the organization informed. on the measures implemented to guarantee the integrity, reliability and compliance of the operations, so the periodic dissemination of internal control activities is not only a communication tool, but also a way to strengthen trust in the organization and maintain a high level of transparency in all operations.

El presente trabajo de investigación, tuvo como objetivo general determinar cuál es la relación del control interno y la gestión de inventarios en la empresa Telecable Iquitos SAC, periodo 2022, investigación de tipo cuantitativa, con tipo de diseño transversal-correlacional y diseño no experimental; tuvo como población de estudio a 76 trabajadores, y registro de informes de control realizados en la empresa Telecable Iquitos SAC, periodo 2022, la investigación concluyo en que existe una correlación muy alta entre la variable control interno y Gestión de inventarios, puesto que los resultados muestran que el grado de correlación está en el rango de 0.80-0.99 (correlación muy alta) siendo una correlación muy significativa ya que el valor de Sig. (bilateral) es 0.01; afirmando que tiene un 99% de nivel de confianza, por lo que se acepta la hipótesis general, además de recomendar a la empresa difundir periódicamente las actividades de control interno, para mantener a todos los involucrados en la organización informados sobre las medidas implementadas para garantizar la integridad, confiabilidad y cumplimiento de las operaciones., por lo que la difusión periódica de las actividades de control interno no solo es una herramienta de comunicación, sino también una forma de fortalecer la confianza en la organización y mantener un alto nivel de transparencia en todas las operaciones.
Keywords: Auditoría interna; Inventarios; Gestión de stocks; Administración de empresas; Empresas; https://purl.org/pe-repo/ocde/ford#5.02.04